Assessment of child and maternal immunization coverage among patients at medical college hospital: A hospital-based cross-sectional study - Ummay Kulsum; Md. Kamrul Hasan (Journal of Sustainability, Society, and Eco-Welfare, 2026)
Background: Immunization is thought to be a very successful and economical therapeutic strategy since it dramatically lowers death and disability from vaccine-preventable illnesses. The survey was carried out at Rangpur medical college hospital (RMCH), Rangpur Division, Bangladesh, with the aim of evaluating the vaccination makeup of kids and moms. Methods: During January and June 2025, systematic interviews and immunisation document checking served to gather information about 200 participants, comprising 120 mothers and 80 children. For the statistical assessment, both deductive and informative techniques were applied using SPSS version 25. Findings: According to the Expanded Programme on Immunisation (EPI) timeline, 65% of the children assessed (n = 80) did totally immunised, 25% did partly immunized, and 10% did none. 55% of mothers received tetanus toxoid (TT) boosters, 78% obtained TT2, and 90% obtained TT1. Mothers in the 20–30 age range showed the highest percentage of vaccination knowledge (65%), followed by those over 30 (55%) and under 20 (40%). Ignorance (42%), vaccine unavailability (28%), fear of complications (18%), and hospital proximity (12%) were the largest obstacles to complete immunization. Furthermore, compared to children from distant regions (45%), children from urban or semi-urban areas had higher full vaccination rates (72%) (p = 0.012). Conclusion: The results underscore the critical role of tailored community-based interventions and policy measures that address structural inequities, maternal empowerment, and healthcare accessibility. To increase equitable levels of vaccination throughout Bangladesh, the results emphasize the necessity of enhancing maternal welfare skills, ensuring that vaccines remain available, and integrating immunizations into routine healthcare for women and newborns. Novelty/Originality of this article: The study additionally explored the interplay of socioeconomic status, maternal education, and health system factors, providing a holistic understanding of immunization behavior and the underlying social determinants influencing vaccine uptake.